(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2006)
This paper describes two casts of a suid from the Late Miocene of Gravitelli (Messina, Sicily), originally described by Seguenza in 1902. The entire Gravitelli faunal collection was lost in the early 1900¡¦s. The recent rediscovery of two casts in the collections of the Museo di Storia Naturale of the University of Florence represent the only available material from this locality (in addition to the original description and illustration by Seguenza). The study of these casts allow a revision of the Gravitelli suid and its attribution to the genus Propotamochoerus. Although a specific determination is not possible, we suggest probable affinities with the species P. hysudricus or P. provincialis.